2024
DOI: 10.35848/1347-4065/ad2747
|View full text |Cite
|
Sign up to set email alerts
|

Stacked structure dependence on resistive switching characteristics in sumanene molecular memory

Ryoichi Kawai,
Eito Ashihara,
Ryousuke Ishikawa
et al.

Abstract: Nonvolatile memories using molecular (molecular memories) are attracting attention. This is because these materials are suitable for miniaturization and higher capacity of memories in terms of the properties and dimensions. We have already demonstrated that the MIM devices with sumanene-inserted bilayer graphene show1) huge resistive switching characteristics. However, the reason why the resistive switching occurs in graphene / sumanene / graphene structure has yet to be clarified. In this work, to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…43,44) Following these theoretical predictions, experimental studies have confirmed that sumanene-intercalated bilayer graphene can operate as a resistive switching device through control over the sumanene conformation with a gate electric field. 45,46) Recently, a unique sumanene derivative, monofluorosumanene, has been synthesized by the substitution of one hydrogen atom terminating the benzylic edges of sumanene by an F atom. 47) Thus, monofluorosumanene has structural asymmetry with respect to the fluorination site in the curved C-C network.…”
Section: Introductionmentioning
confidence: 99%
“…43,44) Following these theoretical predictions, experimental studies have confirmed that sumanene-intercalated bilayer graphene can operate as a resistive switching device through control over the sumanene conformation with a gate electric field. 45,46) Recently, a unique sumanene derivative, monofluorosumanene, has been synthesized by the substitution of one hydrogen atom terminating the benzylic edges of sumanene by an F atom. 47) Thus, monofluorosumanene has structural asymmetry with respect to the fluorination site in the curved C-C network.…”
Section: Introductionmentioning
confidence: 99%